Comparison of conservative treatment of lateral epicondylitis with wrist splint and epicondylitis band: assessing patient compliance and clinical outcomes (Annals of Medical Research, 2023)
Aim: Lateral epicondylitis, commonly known as "tennis elbow," is a prevalent condition affecting middle-aged individuals. The lack of a universally accepted treatment protocol has led to a variety of conservative options, including wrist splints and epicondylitis bands. However, limited research exists comparing the clinical outcomes and patient compliance associated with these two treatment modalities.Materials and Methods: A total of 120 patients diagnosed with lateral epicondylitis were enrolled in this comparative study. Cohort A (n=62) received treatment with a wrist splint, while Cohort B (n=58) received an epicondylitis band. Patient adherence to the prescribed orthosis was monitored during follow-up visits. Clinical outcomes were assessed using the Mayo Elbow Performance Score (MEPS) and Visual Analog Scale (VAS) scores.Results: Patients in Cohort A exhibited significantly higher adherence rates (90.3%) to wrist splint usage throughout the treatment process compared to Cohort B (60.3%) with epicondylitis bands (p
Keywords: Lateral epicondylalgia; Lateral epicondylitis; Patient adherence; Elbow pain; Tendinopathy; Tennis elbow